Rainfall Cistern System Under Rainfed Cultivation of Rice in Poorly Drained Black Soils of Vertisol Group in Chhatisgarh Region - Urkurkar, J S; Sastry, A S.R.A.S; Patel, S R; Chandrawanshi, B R (Annals of Arid Zone, 2016)
Rice crop is grown under rainfed conditions in Chhatisgarh region of Eastern M. P. However, due to high variability of rainfall, rice crop usually fails under rainfed conditions. In view of this an experiment was conducted at Zonal Agriculrural Research Station, (Rice zone), J. N. Agricultural University, Raipur, in the two kharif seasens of 1981 and 1982. The rainfall cistern system is a series of raised and sunken bed system. In raised bed soybean crop and in sunken bed rice crop of early duration variety were grown. The study revealed that about 46 per cent of rainfall from raised bed is collected as induced runoff in the sunken bed. The econometrics of the rainfall cistern system was also analysed.